Assessing affect in adolescents with e-diaries: multilevel confirmatory factor analyses of different factor models - Limberger, Matthias F.; Schmiedek, Florian; Santangelo, Philip S.; Reichert, Markus; Wieland, Lena M.; Berhe, Oksana; Meyer-Lindenberg, Andreas; Tost, Heike; Ebner-Priemer, Ulrich W. (Frontiers in Psychology, 2023)
In the last two decades, e-diary studies have gained increasing interest, with a dominant focus on mood and affect. Although requested in current guidelines, psychometric properties are rarely reported, and methodological investigations of factor structure, model fit, and the reliability of mood and affect assessment are limited. We used a seven-day e-diary dataset of 189 adolescent participants (12–17  years). The e-diary affect assessments revealed a considerable portion of within-person variance. The six-factor model showed the best model fit compared to the less complex models. Factor loadings also improved with the complexity of the models. Accordingly, we recommend that future e-diary studies of adolescents use the six-factor model of affect as well as reporting psychometric properties and model fit. For future e-diary scale development, we recommend using a minimum of three items per scale to enable the use of confirmatory multilevel factor analyses.